Performances on the Timed Up and Go Test and subtasks between fallers and non-fallers in older adults with cognitive impairment - Ansai, Juliana Hotta; Andrade, Larissa Pires de; Nakagawa, Theresa Helissa; Rebelatto, José Rubens (Arquivos de Neuro-Psiquiatria, 2018)
This work aimed to compare performances on the Timed Up and Go (TUG) test and its subtasks between faller and non-faller older adults with mild cognitive impairment (MCI) and mild Alzheimer’s disease (AD). A prospective study was conducted, with 38 older adults with MCI and 37 with mild AD. Participants underwent an assessment at baseline (the TUG and its subtasks using the Qualisys ProReflex system) and the monitoring of falls at the six-month follow up. After six months, 52.6% participants with MCI and 51.3% with AD fell. In accordance with specific subtasks, total performance on the TUG distinguished fallers from non-fallers with AD, fallers from non-fallers with MCI and non-fallers with MCI from non-fallers with AD. Although no other difference was found in total performances, non-fallers with MCI and fallers with AD differed on the walking forward, turn and turn-to-sit subtasks; and fallers with MCI and non-fallers with AD differed on the turn-to-sit subtask.
Keywords: aged; Alzheimer’s disease; accidental falls; cognitive disfunction